Population pharmacokinetics of methotrexate in paediatric patients with acute lymphoblastic leukaemia and malignant lymphoma. (4th March 2022) - Zhan, Min; Sun, Yiqi; Zhou, Fang; Wang, Honghong; Chen, Zebin; Yan, Lianzhen; Li, Xingang
Abstract: This study aimed to identify physiological and pharmacogenomic covariates and develop a population pharmacokinetic model of high-dose methotrexate (HD-MTX) in Chinese paediatric patients with acute lymphoblastic leukaemia (ALL) and malignant lymphoma. A total of 731 MTX courses and 1658 MTX plasm concentrations from 205 paediatric patients with ALL and malignant lymphoma were analysing using a non-linear mixed-effects model technique. 47 SNPs in 16 MTX-related genes were genotyped and screened as covariates. A PPK model was established to determine the influence of covariates, such as body surface area (BSA), age, laboratory test value, and SNPs on the pharmacokinetic process of HD-MTX. Two-compartmental model with allometric scaling using BSA could nicely characterise the in vivo behaviour of HD-MTX. After accounting for body size, rs17004785 and rs4148416 were the covariates that influence MTX clearance (CL). The PPK model obtained was: CL = 9.33 * (BSA/1.73) 0.75 * e 0.13*rs17004785 * e 0.39*rs4148416 * e ηCL, Vc = 24.98 * (BSA/1.73) * e ηvc, Q  = 0.18 * (BSA/1.73) 0.75 * e ηQ and Vp = 4.70 * (BSA/1.73) * e ηvp . The established model combined with the Bayesian approach could estimate individual pharmacokinetic parameters and optimise personalised HD-MTX therapy for paediatric patients with ALL and malignant lymphoma.